Spurring digital transformation in Singapore's legal industry - CHUA, Xin Juan (Institutional Knowledge at Singapore Management University, 2021)
COVID-19 has transformed the way we live and work. It has caused the processes and operations of businesses and organisations to be restructured, as well as transformed business models. A 2020 McKinsey Global survey reported that companies all over the world claim they have accelerated the digitalisation of their customer and supply-chain interactions, as well as their internal operations, by three to four years. They also said they thought the share of digital or digitally enabled products in their portfolios has advanced by seven years. While technology transformation is not new to the legal profession, COVID-19 has cemented the importance of technology and further mainstreamed its use in the delivery of legal services. Many lawyers now access and work on their case files from home through virtual workspaces. It has become de rigueur for court and arbitration hearings, as well as mediation sessions, to be conducted in either a fully virtual or hybrid manner. Even as we look forward to moving away from the spectre of COVID-19, the changes it has wrought in legal technology transformation are here to stay. The question is: how can lawyers, law firms, legal industry and the broader legal ecosystem be prepared for, and benefit from, these changes?